Penguatan Karakter Profil Pelajar Pancasila Berbasis Kearifan Lokal Jenjang SMP Di Mojokerto - Suesthi Rahayuningsih; Asih Andriyati Mardliyah; Achmad Rijanto (CV. Multi Kreasi Media, 2024)
Community Partnership Empowerment was implemented at SMP Negeri 2 Kemlagi, Mojokerto, East Java. The partner's problem is that there is still a lack of knowledge about the character of the Pancasila student profile based on local wisdom according to the school context. The aim of this service is to increase the knowledge of teachers and school principals in understanding the character education of Pancasila student profiles based on local wisdom according to the school context through the use of the independent teaching platform. The method of service carried out is by providing reinforcement to teachers and school principals regarding Pancasila student profile character education based on local wisdom according to the school context using an independent teaching platform in the form of training. The results obtained from this service are from the evaluation results of the participant attendance level being 100%, while the percentage increase in partner knowledge in using the independent teaching platform to increase the capacity of teachers and school principals related to strengthening the character of Pancasila student profiles based on local wisdom according to the context and needs of the school shows that the results are increasing the capacity of training participants by 80%.